The Compoundness and Sequentiality of Digital Inequality - Alexander van Deursen; Ellen Helsper; Rebecca Eynon; Jan van Dijk (International journal of communication, 2017)
Through a survey with a representative sample of Dutch Internet users, this article examines compound digital exclusion: whether a person who lacks a particular digital skill also lacks another kind of skill, whether a person who does not engage in a particular way online is also less likely to engage in other ways, and whether a person who does not achieve a certain outcome online is also less likely to achieve another type of outcome. We also tested sequential digital exclusion: whether a lower level of digital skills leads to lower levels of engagement with the Internet, resulting in a lower likelihood for an individual to achieve tangible outcomes. Both types of digital exclusion are a reality. Certain use can have a strong relation with an outcome in a different domain. Furthermore, those who achieve outcomes in one domain do not necessarily achieve outcomes in another domain. To get a comprehensive picture of the nature of digital exclusion, it is necessary to account for different domains in research.